Revisitando solidaridad: Perspectivas en un nuevo orden mundial - Oscar Javier Montiel Mendez; Miliausha Sirazetdinova (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales)
Solidarity as a social construct has begun to take up new momentum in the social sciences. It has enormous potential to impact all of its areas, especially management. In this article, we, guest editors, introduce various perspectives that shed light on how to apply to different theoretical and empirical concerns, which were part of the special issue dedicated to this topic in Telos. The purpose of this study is to analyze the directions and approaches in contemporary studies of social solidarity. The authors use analysis of secondary source and theoretical analysis of sociological, economic, and managerial concepts. Another classification of sources divide those regarding theoretical issues of joint society, and exploring solidarization practices. The research findings show that traditional concepts of social systems’ integration and collective satisfaction of needs neighbor with numerous contexts arising around solidarity as a human right to collective protection of group interests, an ethical obligation to help those who are in need, acceptance of the Other, contributing to global integration.